Antibacterial Efficacy of Two Commercially Available Bacteriophage Formulations, Staphylococcal Bacteriophage and PYO Bacteriophage, Against Methicillin-Resistant Staphylococcus aureus: Prevention and Eradication of Biofilm Formation and Control of a Systemic Infection of Galleria mellonella Larvae - Tkhilaishvili, Tamta; Wang, Lei; Tavanti, Arianna; Trampuz, Andrej; Di Luca, Mariagrazia (Frontiers in Microbiology, 2020)
Sessile bacteria growing on surfaces are more resistant to standard antibiotics than their planktonic counterpart. Due to their antimicrobial properties, bacteriophages have re-emerged as a promising approach to treat bacterial biofilm-associated infections. Here, we evaluated the ability of two commercially available phage formulations, Staphylococcal bacteriophage (containing the monophage Sb-1) and PYO bacteriophage (a polyphage), in preventing and eradicating an in vitro biofilm of methicillin-resistant Staphylococcus aureus (MRSA) by isothermal microcalorimetry and high-resolution confocal laser scanning microscopy. Moreover, to assess the potential in vivo efficacy of both phage preparations a Galleria mellonella model of MRSA systemic infection was used. Microcalorimetry measurement showed that 107 PFU/ml (the highest tested titer) of both phage formulations were able to inhibit planktonic growth in a concentration-dependent manner. However, MRSA biofilm was eradicated only by co-incubation of 5-7 days with the highest phage titers, respectively. In the experiments of biofilm prevention, isothermal microcalorimetry revealed the heat production was completely abolished in the presence of sub-inhibitory titers (104 PFU/ml) of phages. These data were also confirmed by confocal laser scanning microscopy. Both phage formulations increased the survival of G. mellonella larvae preventing or treating MRSA infection compared to untreated control. In conclusion, tested phage formulations are promising for preventing device colonization and killing biofilm bacteria attached on a surface. Novel strategies for direct coating and release of phages from material should be investigated.